The development and validation of the Penta Helix construct - Kiki Sudiana; Ernie Tisnawati Sule; Imas Soemaryani; Yunizar Yunizar (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The concept of Penta Helix or Quintuple Helix have been widely discussed and used as frameworks in many researches in relation of innovation or organizational innovation field. It is believed that if the Penta Helix stakeholders work together in synergy it will foster innovation and an innovation-based economy. However, no research has been found yet that validate measurement constructs of the Penta Helix or the Quintuple Helix. Through extensive literature review, we developed a construct of the Penta Helix variables in relation to innovation and knowledge-based economy, into five dimensions consisting of Academicians, Business, Government, Community and Medias (ABGCM). The data was collected through a questionnaire distributed to 95 technology-based startups in Indonesia, and afterward analysed by using confirmatory factor analysis technique, performed by the SmartPLS software. A final 20-item measurement construct was validated as main contribution of this study toward Penta Helix theory. There are issues arose on methodological and theoretical of the Penta Helix construct and discussed in our findings.
Keywords: A13; C31; C52; O32; L26; 650; Penta Helix Construct; confirmatory factor analysis; construct validity; Validity Penta Helix